The effect of coconut water and naphthalene acetic acid (NAA) application on the in vitro growth of Paraphalaeonopsis serpentilingua from West Kalimantan - MUKARLINA MUKARLINA; AGUSTINA LISTYAWATI; SRI MULYANI (Smujo International, 2010)
Abstract. Mukarlina, Listiawati A, Mulyani S. 2010. The effect of coconut water and naphthalene acetic acid (NAA) application on the in vitro growth of Paraphalaeonopsis serpentilingua from West Kalimantan. Nusantara Bioscience 2: 62-66. The ‘Ekor tikus’ orchid (Paraphalaenopsis serpentilingua J.J. Sm.) is an epidemic orchid in West Kalimantan. Now this orchid is facing a great conservation problem and threatened to be in extinction due to human exploitation. This research was conducted to find out the in vitro growth effect of P. serpentilingua by supplementation of NAA and coconut water in culture medium. The experiment was carried out using a Completely Randomized Design with two factors and five replicates. The result showed that supplemented NAA and coconut water on MS medium affected the emergence timing of buds, the average buds number, the average leaf number/buds, percentage of buds, the emergence timing of root, average root number and percentage of root. Medium that supplemented with 1.5 ppm NAA and 10% coconut water showed the fastest emergence timing of apical bud that is 13 days after planting. Medium supplemented with 0.5 ppm of NAA and 7.5% of coconut water shown the highest average number of bud was 11 buds.